LncRNA GAS5 participates in childhood pneumonia by inhibiting cell apoptosis and promoting SHIP-1 expression via downregulating miR-155 - Xiaoping Wang (BMC, 2021)
Abstract Background LncRNA GAS5 and miR-155 are reported to play opposite roles in lung inflammatory responses. Lung inflammation participates in childhood pneumonia, indicating the involvement of GAS5 and miR-155 in pneumonia. The study aimed to analyze the potential interaction between GAS5 and miR-155 in childhood pneumonia. Methods GAS5 and miR-155 levels in plasma samples from pneumonia patients and controls were detected using RT-qPCR. The role of GAS5 in miR-155 RNA gene methylation in human bronchial epithelial cells (HBEpCs) was analyzed by methylation analysis. Flow cytometry and RT-qPCR were applied to analyze cell apoptosis and SHIP-1 expression, respectively. Results GAS5 was downregulated in pneumonia, and miR-155 was upregulated in pneumonia. GAS5 and miR-155 were inversely correlated. GAS5 overexpression decreased miR-155 expression in HBEpCs, while miR-155 overexpression showed no significant effects on GAS5 expression. In addition, GAS5 suppressed LPS-induced HBEpC apoptosis, promoted SHIP-1 expression, and reduced the enhancing effect of miR-155 on cell apoptosis and SHIP-1 expression. Conclusions GAS5 may participate in childhood pneumonia by inhibiting cell apoptosis and promoting SHIP-1 expression via downregulating miR-155.